2023
DOI: 10.1002/ehf2.14364
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of transthyretin amyloidosis among heart failure patients with preserved ejection fraction in Japan

Abstract: Aims Heart failure with preserved ejection fraction (HFpEF), which is caused by wide various conditions, has become a major public health problem. Transthyretin amyloid cardiomyopathy (ATTR‐CM), which is thought to be an underdiagnosed disease, can cause HFpEF. Non‐invasive diagnosis using 99mTechnetium (Tc)‐pyrophosphate (PYP) scintigraphy enables accurate diagnosis of ATTR‐CM. The aim of this study was to clarify the prevalence and characteristics of ATTR‐CM among Japanese patients with HFpEF. Methods and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In a recently published Japanese multi-centre registry, 14.2% of patients with HFpEF who underwent bone scintigraphy regardless of LV wall thickness were diagnosed with ATTR-CM. [34] Meanwhile, in data from China, the prevalence of ATTR-CM in patients with HFpEF or HFmrEF with an LV wall thickness > 12 mm was approximately 5.3%, which was signi cantly lower than that reported among Western populations. [35] Among Asian populations, only one multinational study identi ed the common genetic variation and phenotypic characteristics of hereditary TTR amyloidosis in a Southeast Asian cohort.…”
Section: Discussionmentioning
confidence: 85%
“…In a recently published Japanese multi-centre registry, 14.2% of patients with HFpEF who underwent bone scintigraphy regardless of LV wall thickness were diagnosed with ATTR-CM. [34] Meanwhile, in data from China, the prevalence of ATTR-CM in patients with HFpEF or HFmrEF with an LV wall thickness > 12 mm was approximately 5.3%, which was signi cantly lower than that reported among Western populations. [35] Among Asian populations, only one multinational study identi ed the common genetic variation and phenotypic characteristics of hereditary TTR amyloidosis in a Southeast Asian cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, ATTR-CA can mimic other forms of hypertrophic and restrictive cardiomyopathy (3). Studies published over the past decade, mainly in western countries, indicate that ATTR-CA is more common than previously believed and that it is significantly underdiagnosed (4)(5)(6)(7)(8). The emergence of novel disease-modifying therapies has led to a global effort to improve the diagnosis and management of ATTR-CA (9).…”
Section: Introductionmentioning
confidence: 99%
“…Bone scintigraphy enables the diagnosis of cardiac ATTR amyloidosis in patients who do not have a monoclonal gammopathy [ 13 ]. Recent studies found that by using this method, the prevalence of cardiac ATTR amyloidosis in patients with heart failure with a preserved ejection fraction is 13–18% [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%